Design and simulation of a multihoming-based inter-system handoff scheme in NEMO - Islam, Shayla (Kauno Technologijos Universitetas, 2016)
A method is developed for reducing the power inverter electrical circuit of fourth order to an electrical network of second order. The reduction is based on the assumption that the output inverter voltage is practically with a sine-wave shape. The normalized form guarantees novelty and versatility of the investigation on one hand and independency in relation to the concrete inverter parameters like output power, supplying voltage and operating frequency on the other. From the whole power network of fourth order for the first time two sub circuits are suggested to be outlined: the output (load) sub circuit and the inverter commutating sub circuit. Both sub circuits of a second order define the parameters of the endmost inverter circuit again of the same order and consequently the mode of operation and parameters of the power inverter itself. The transformation is possible owing to the newly found fact that the frequency dependencies of the output (load) sub circuit can be separated from the dependencies that describe the structural relationships between the two sub circuits. The results from that conversion are of course more accurate when the resonant frequencies of the both sub circuits and the operating frequency do not differ substantially. The suggested approach is useful on order to obtain a simplified engineer method for precise and fast design of large class of static power converters applicable in electronic technology like induction heating and melting.